Urban bus driver ride and road–friendliness. Part II: subjective suspension damping tuning and objective optimisation. (6th March 2012) - Cao, Dongpu; Rakheja, Subhash; Wang, Zhanqi
Three–dimensional ride dynamic model of an urban bus, developed in first part of the study, is applied to determine desirable suspension damping through subjective tuning and objective parametric optimisation under a wide range of operating conditions, including vehicle speed, load, road roughness and tyre inflation pressure. While the subjective method relies on the motion perception of the experimenter, the objective approach is limited to performance measures considered in the optimisation problem. The results suggest that both the objective and subjective methods could yield enhanced driver ride and dynamic tyre loads over the most probable ranges of operating conditions when compared with the baseline dampers. The ride responses of the candidate bus equipped with subjectively tuned dampers were subsequently measured, which further demonstrated applicability of the model for suspension damping tuning for enhancing both the driver– and road–friendliness.